PERSONAL SELLING AND DIGITAL MARKETING AS CRUCIAL FACTORS IN MAXIMIZING CUSTOMER SATISFACTION THROUGH PERCEIVED VALUE IN THE USAGE OF M-BANKING APPLICATION - Sembhodo, Abimanyu Tuwuh; Hermawati, Adya; Fatmawati, Endang; Junaedi, I Wayan Ruspendi; Ali, Shujahat (Universitas Brawijaya, Indonesia, 2022)
The use of mobile banking applications supports the level of customer satisfaction of BPR Lembah Artha. The growth in the use of mobile banking shows customer satisfaction and the success of digital marketing. The research aims to find out that the relationship between personal selling and digital marketing can increase perceived value, personal selling relationships, digital marketing, and the perceived value of users of mbanking applications users. Perceived value can mediate personal selling on customer satisfaction, and perceived value can mediate digital marketing on satisfied customers. The quantitative approach is used as a research approach. Data were collected by questionnaire. The data collected were analyzed to determine the effect between variables, and the analysis technique was Partial Least Square (PLS). The research was conducted at BPR Lembah Artha. The research subjects are BPR Lembah Artha customers who use the Mobile Banking application. The object of research is a review of the effect of personal selling and digital marketing on customer satisfaction by mediating value perceptions. The sampling technique is purposive sampling. The results show that personal selling and digital marketing affect perceived value; personal selling, digital marketing, and perceived value affect satisfaction. Perceived value can mediate the effect of personal selling on customer satisfaction/users of the m-banking application. Perceived value can mediate the effect of digital marketing on customer satisfaction/users of the m-banking application. Better personal selling and digital marketing can improve customer perceptions of value. Good value perception is indicated by customer satisfaction and supports personal selling.